COGNITIVE DECLINE: KNOWLEDGE, ATTITUDES AND PREVENTIVE PRACTICES OF OLDER ADULTS IN THE COMMUNITY - Priscila Aguiar Mendes; Annelita Almeida Oliveira Reiners; Rosemeiry Capriata de Souza Azevedo; Ana Carolina Macri Gaspar; Neuber José Segri (Universidade Federal do Paraná, 2018)
Objective: to evaluate the knowledge, attitudes and practices for the prevention of cognitive decline carried out by older adults. Method: a cross-sectional study was carried out with 557 older adults attended at the Family Health Units of a municipality of Mato Grosso from February to May of 2015. The data were collected through an interview using a structured questionnaire with questions on knowledge, attitudes and practices for the prevention of cognitive decline based on Knowledge, Attitude and Practice surveys. A bivariate analysis was performed between the variables knowledge, attitudes and practices for the prevention of cognitive decline, as well as Poissonmultiple regression by the forward stepwise method. Results: 469 (84.2%) of the older adults presented unsatisfactory knowledge; 523 (93.9%) a favorable attitude; and 307 (55.1%) performed practices to prevent cognitive decline. An association was found between satisfactory knowledge and practices for the prevention of cognitive decline (p=0.027). Conclusion: These findings provide support for health actions that aim to increase the performance of preventive practices in this population.